Sick Surgeon: Problem and the panacea! - Ghimire, Bikal (Journal of Society of Surgeons of Nepal, 2018)
Gautam Buddha has rightly said ‘To keep the body in good health is a duty... otherwise we shall not be able to keep our mind strong and clear’. We need clear minds as a clinician and more so as surgeon to plan the course of treatment and to physically execute it. However, apart from clear minds a surgeon should also be physically capable to withstand strenuous activities for long periods of time. Daily exertion for prolog periods for surgeons leads to poor quality of life especially in our subcontinent where health institutions and the government do not prioritize the health of clinicians.